Pemanfaatan Kajian Tuturan Pemanduan Wisata Kopi-Kakao dalam Pembelajaran Keterampilan Berbicara - Rusdhianti Wuryaningrum; Arju Muti'ah; Arief Rijadi (Universitas Indraprasta PGRI Jakarta, 2021)
This study describes the use of tour guide discourse on speaking learning in formal forums. This is a descriptive research (qualitative). The research data were obtained by recording direct speech, speaking skills test to Indonesian MKWU students, University of Jember in 2021, even semester. Data analysis was performed with descriptions, interpretations, and explanations. The results showed a rhetorical pattern of the guidance discourse of coffee-cocoa educational tours that can be applied in speaking learning, namely (1) speech descriptions, (2) calcification analysis, (3) complex procedures analysis, (4) contexts evaluation or phenomena. The four patterns were applied in text-based learning syntax at the core of learning. Through text studies, students obtained a complete speech model in conveying information. This was confirmed by the evaluation results of good category (that meets 3 indicators) on all aspects.